Students' Difficulties in Achieving Effective English Learning - Juliansyah, Roni (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
English is an important foreign language to learn. This language is international and is used in various countries including Indonesia. In fact, in its application there are still many problems faced for both teachers and students during the learning process. Many reactions are be established in the learning process towards these difficulties, especially on students' outlooks in the learning process, results of students’ learning, and contribution in carrying out set of activities. This research purposes to explain the students’ problems in the process of English learning and the reasons that influence it. This research applies a qualitative approach such as questionnaire instruments, observations, and recording of video. The research data analysis is carried out through three procedures, they are reduction of data, presentation of data, description of conclusion and confirmation. The outcomes revealed that the subjects of research had various difficulties in learning English.